Automated E-Counseling for Chronic Heart Failure: CHF-CePPORT Trial. (January 2021) - Nolan, Robert P.; Ross, Heather J.; Farkouh, Michael E.; Huszti, Ella; Chan, Sammy; Toma, Mustafa; D'Antono, Bianca; White, Michel; Thomas, Scott; Barr, Susan I.; Perreault, Sylvie; McDonald, Michael; et al.
Abstract : Background: International task force statements advocate telehealth programs to promote health-related quality of life for patients with chronic heart failure (CHF). To that end, we evaluated the efficacy and usability of an automated e-counseling program. Methods: This Canadian multi-site double-blind randomized trial assessed whether usual care plus either internet-based e-counseling (motivational and cognitive-behavioral tools for CHF self-care) or e-based conventional CHF self-care education (e-UC) improved 12-month Kansas City Cardiomyopathy Questionnaire Overall Summary (KCCQ-OS). Secondary outcomes included program engagement (total logon weeks, logons, and logon hours), total CHF self-care behaviors, diet (fruit and vegetable servings), 6-minute walk test, and 4-day step count. The association between program engagement and health-related quality of life was assessed using KCCQ-OS tertiles. Results: We enrolled 231 patients, median age =59.5 years, 22% female, and elevated median KCCQ-OS=83.0 (interquartile range, 68–93). KCCQ-OS increase ≥5 points was not more prevalent for e-counseling, n=29 (29.6%) versus e-UC, n=32 (34.0%), P =0.51. E-Counseling versus e-UC increased total logon weeks ( P =0.02), logon hours ( P =0.001), and logons ( P <0.001). Only e-counseling showed a positive association between 12-month KCCQ-OS tertile and logon weeks ( P =0.04) and logon hours ( P =0.004). E-Counseling increased CHF self-care behavior and diet but not 6-minute walk test or 4-day step count. Conclusions: The primary KCCQ-OS end point was negative for this trial. Only e-counseling showed a positive association between program engagement and 12-month KCCQ-OS tertile, and it improved CHF self-care behavior and diet. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01864369. Abstract : Supplemental Digital Content is available in the text.